Integrated CFD investigation of heat transfer enhancement using multi-tray core catcher in SFR. (June 2017) - Rakhi; Sharma, Anil Kumar; Velusamy, K.
Highlights: Heat transfer enhancement using multi-tray core catcher for SFR is investigated. The capability of a single core collector tray is estimated. Double and triple collector trays with innovative designs is discussed. Provision of openings in the trays contributed to enhanced natural circulation. Abstract: To render future SFR more robust and safe, certain BDBE have been considered in the recent years. A Core Disruptive Accident leading to a whole core meltdown scenario has gained the interest of researchers. Various design concepts and safety measures have been suggested and incorporated in design to address such a low probability scenario. A core catcher concept, in particular, has proved to be inevitable as an in-vessel core retention device in SFR for safe retention of core debris arising out after the severe accident. This study aims to analyse the cooling capability of the innovative design concept of core catcher to remove decay heat of degraded core after the accident. First, the capability of single collection tray is established and then the study is extended to two and three collection trays with different design concepts. Transient forms of governing equations of mass, momentum and energy conservations along with k-ε turbulence model are solved by finite volume based CFD solver. Boussinesq approximation is invoked to model buoyancy in sodium. The study shows that a single collection tray is capable of removing up to 20 MW decay heat load in a typical 500 MWe pool type SFR. Further, studies are carried out to improve the natural circulation of sodium around the source, in the lower plenum and to distribute core debris of the whole core to multiple collection trays. It is found that the double and triple collection trays can accommodate decay loads up to 29 MW. Provision of openings in the collection trays has proved to be effective in improving the heat transfer and sodium flow as well as in distributing the core debris to the successive plates. Detailed analysis of isotherms and velocity field in the multiple collection trays with openings reveals improved natural circulation in and around the collection trays in the lower plenum. A three tray core catcher device with multiple openings can accommodate the decay heat of whole core meltdown, without exceeding the safe temperature limits of structural material. Special attention has been paid to the space constraint in the lower plenum while incorporating the three tray core catcher device.